A novel strategy for the discrimination of gelatinous Chinese medicines based on enzymatic digestion followed by nano-flow liquid chromatography in tandem with orbitrap mass spectrum detection - Yang, Huan (2015)
Gelatinous Chinese medicines made from mammalian skin or horn or reptile shell are a very important type of animal-derived Chinese medicine. They have been extensively used either as both hemopoietic and hemostatic agents to treat vertigo, palpitation, hematuria, and insomnia in traditional Chinese medicine clinics; consumed as a popular tonic for weaker persons such as the elderly or women after giving birth; or further manufactured to health supplements for certain populations. However, they cannot be discriminated from each other by only using the routine approach in the Chinese Pharmacopoeia, as it lacks enough specificity and, consequently, and the requirements can be met even by adding assayed ingredients. In this study, our efforts to differentiate three gelatinous Chinese medicines, Asini Corii Colla, Cervi Cornus Colla, and Testudinis Carapacis ET Plastri Colla, are presented, and a novel strategy based on enzymatic digestion followed by nano-flow liquid chromatography in tandem with orbitrap mass spectrum detector analysis is proposed herein. Fourteen diagnostic fragments identified from the digests of these medicines were exclusively selected for their discrimination. By taking advantage of the favorable features of this strategy, it is feasible and convenient to identify enzymatic-digested peptides originated from signature proteins in each medicine, which thus could be employed as potential biomarkers for their form of raw medicinal material, and the pulverized and the complex especially, that being the direct basis for authentication purpose.